A Stroop in the Hand is Worth Two on the Laptop: Superior Reliability of a Smartphone Based Alcohol Stroop in the Real World. (21st March 2019) - Spanakis, Panagiotis; Jones, Andrew; Field, Matt; Christiansen, Paul
Abstract: Background : Attentional bias (AB) is the tendency for substance-related stimuli to grab attention. The addiction Stroop task is widely used for measuring AB in the lab, but it has poor reliability and inconsistent predictive validity. Therefore, there is a need to improve the psychometric properties of the task. Objectives: This study contrasts the internal reliability and predictive validity of a basic (general alcohol words) and an upgraded (personalized alcohol pictures) Stroop task delivered in a neutral room on a laptop computer versus a smartphone application on participants' homes. Methods : 120 participants recruited in 2016, completed a basic and an upgraded Stroop task. Half the participants completed the tasks on a laptop computer in a neutral university room and the remainder completed the tasks on a smartphone app in their homes. Participants also self-reported their typical alcohol consumption. Results : Acceptable internal reliability was found for both basic ( α = .70) and upgraded ( α = .74) Stroop tasks in the home-smartphone condition, but neither had acceptable internal reliability when administered in the neutral room-computer condition (basic α = .49; upgraded α = .58). Participants showed AB toward alcohol words, but not for beer pictures, regardless of condition. None of the indices of AB was associated with individual differences in alcohol involvement, regardless of condition. Conclusion : The internal reliability of the alcohol Stroop was acceptable when administered on smartphones, in naturalistic settings, rather than on laptop computers, in neutral university rooms.